Marcuse - McNulty, Jacob 1989- (Routledge, 2025)
"Herbert Marcuse (1898-1979) is known to many as a leading figure of 1960s counter-culture, and a 'Guru of the New Left'. However, the deeper philosophical background to Marcuse's thought is often forgotten, especially his significant engagement with German idealism, ancient philosophy, and a broad spectrum of problems and issues from the philosophical tradition. This much-needed book introduces and assesses Marcuse's philosophy and is ideal for those coming to his work for the first time. Jacob McNulty covers the following topics: Marcuse's life and the background to his thought, including his formative period as a student of Husserl and Heidegger and as a philosopher in Horkheimer's institute Marcuse's recasting of metaphysics in light of Marxian and Freudian thought Marcuse and German idealism, especially the role of Kant and Hegel Marcuse's philosophy of human nature, his use of the late Freud's ideas of Eros and Thanatos Marcuse as a critic of state and monopoly capitalism Meaning, propaganda, and ideology: the political implications of language and also the centrality of free speech Marcuse's aesthetics Marcuse's legacy and his relationship to contemporary analytical philosophy (especially "analytic critical theory"). An outstanding and engaging introduction to a central figure in twentieth-century radical thought, Marcuse is essential reading for those in philosophy and related disciplines including political theory, sociology and media and communication studies"--